Assessing the effects of reaction variables for enhanced chromium(III) adsorption efficiency using beidellite clay - Abduraboh Alraae; Ali Moussadik; Abdellah Benzaouak; Mohammed Kacimi; Mohammed Dahhou; Aicha Sifou; Adnane El Hamidi (Results in Surfaces and Interfaces)
The mineralogical and chemical composition of beidellite was characterized using X-ray fluorescence (XRF), X-ray diffraction (XRD), thermogravimetric analysis (TGA/DTA), SEM-EDX analysis, and infrared spectroscopy (IR). The cation exchange capacity (CEC) and specific surface area (SSA) were determined to be 89.80 meq/100 g and 65 m2.g−1, respectively, using the ammonium acetate method and Brunauer-Emmett-Teller (BET) analysis. The adsorption properties of beidellite for Cr3+ removal from aqueous solutions were systematically investigated, focusing on the effects of contact time, pH, adsorbent mass, and initial Cr3+ concentration. The results revealed that Cr3+ adsorption was highly efficient at pH values above 4, achieving near-complete removal (>99 %) within 30 min. The adsorption efficiency was optimal at pH 4–6, where electrostatic interactions and surface complexation were maximized. Higher pH values led to the precipitation of chromium hydroxide, reducing adsorption efficiency. The adsorbent mass and initial Cr3+ concentration also significantly influenced the process, with 0.1 g of beidellite achieving >99 % removal for Cr3+ concentrations below 53.3 mg.L−1. Experimental data were modeled using Langmuir, Freundlich, and Sips isotherms, with the Langmuir model providing the best fit (R2 = 0.971), indicating homogeneous monolayer adsorption. The maximum adsorption capacity (Qm) was calculated to be 63.935 mg.g−1. Kinetic studies revealed that the adsorption process followed pseudo-second-order kinetics (R2 = 0.9986), suggesting chemisorption as the rate-limiting step.The study highlights the effectiveness of beidellite as a cost-efficient and environmentally friendly adsorbent for Cr3+ removal, offering rapid kinetics, high adsorption capacity, and optimal performance across a broad pH range. These findings provide valuable insights for the application of beidellite in wastewater treatment, particularly in industries affected by chromium pollution.